PENGARUH LINGKUNGAN KERJA, NILAI-NILAI SOSIAL, PERTIMBANGAN PASAR KERJA, DAN PERSONALITAS PADA PEMILIHAN KARIR AKUNTAN PUBLIK - Talamaosandi, Ni Komang Putri Sari; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 19 No 1 (2017), 2017)
The purpose of this study was to determine the influence of the working environment, social values, consideration of the labor market, and personality in the perception of career choice of students majoring in accounting as a public accountant. This study uses primary data was collected by using a questionnaire as an instrument of data with the respondents is the final semester students (6th semester and above) accounting department Faculty of Economics and Business Program Extension of Udayana University. The samples used were 100 students by using probability sampling methods. Data analysis technique used by multiple linear regression analysis. The result showed that the working environment, social values, consideration of the labor market, and personality has positive significant effect on the selection of career as a public accountant.
Keywords: working environment, social values, labor market consideration, personality, public accountant